Sir Henry Sumner Maine et les systemes juridiques traditionnels - Hamza, Gábor (Díké - A Márkus Dezső Összehasonlító Jogtörténeti Kutatócsoport folyóirata, 2024)
The birth of comparative law in England is strongly linked with the Ancient Law, its Connection with the Early History of Society and its Relation to Modern Ideas, of Sir Henry Sumner Maine published in 1861. Maine is the first in England to be endowed ‘ad personam’ with the Chair of Comparative Law in Oxford in order to teach legal history and comparative (foreign) law. It is undoubtedly the Roman law that stood in the focus of interest of Sir Henry Sumner Maine serving as basis to carry out comparative legal studies. That approach is in particular manifested in Ancient Law as Maine attributes significance to the various institutions of Roman law. The author draws in particular a comparison between Maine and Bachofen as far as their approach relating to the basis of foreign law related research is concerned. The role that Roman law (ius Romanum), i.e. Civil law (ius civile), played in the development of English law during the centuries is also underlined in this paper, and in its last part, the author emphasizes the contemporary significance of Ancient Law and traditional legal systems for the foreign law related research on the basis of the works of Maine.